Absence of back to school peaks in human rhinovirus detections and respiratory symptoms in a cohort of children with asthma. Issue 4 (8th September 2015) - Stelzer‐Braid, Sacha; Tovey, Euan R.; Willenborg, Christiana M.; Toelle, Brett G.; Ampon, Rose; Garden, Frances L.; Oliver, Brian G.; Strachan, Roxanne; Belessis, Yvonne; Jaffe, Adam; Reddel, Helen K.; Crisafulli, Daniel; et al.
Abstract : Much of what is known about the seasonality of human rhinovirus (hRV) infections has been learned from the study of acute asthma exacerbations presenting to emergency care, including those among children at the start of the school term. Much less is known about the patterns of hRVs in the community. In this study, viruses and day‐to‐day symptoms of asthma and colds were monitored twice weekly in 67 children with asthma aged 5–12 years, over a 15 month period in Sydney, Australia. Overall hRV was detected in 314/1232 (25.5%) of nasal wash samples and 142/1231 (11.5%) of exhaled breath samples; of these, 231 and 24 respectively were genotyped. HRVs were detected with similar prevalence rate throughout the year, including no peak in hRV prevalence following return to school. No peaks were seen in asthma and cold symptoms using twice‐weekly diary records. However, over the same period in the community, there were peaks in asthma emergency visits both at a large local hospital and in state‐wide hospitalizations, following both return to school (February) and in late autumn (May) in children of the same age. This study suggests that hRV infections are common throughout the year among children, and differences in virus prevalence alone may not account for peaks in asthma symptoms. J. Med. Virol. 88:578–587, 2016 . © 2015 Wiley Periodicals, Inc.